Diamond/carbon nanotube composites: Raman, FTIR and XPS spectroscopic studies. (January 2017) - Varga, Marian; Izak, Tibor; Vretenar, Viliam; Kozak, Halyna; Holovsky, Jakub; Artemenko, Anna; Hulman, Martin; Skakalova, Viera; Lee, Dong Su; Kromka, Alexander
Abstract: As long as the carbon family materials are pristine, powerful methods for their individual characterization have been established and well understood. However, as soon as these materials contain a mixture of sp 2 and sp 3 hybridized carbons, the spectroscopic characterization becomes challenging. In this paper we present on some aspects of multiply spectroscopic characterizations of sp 2 -sp 3 carbon heterosystems, which can play an important role for their correct structural assignment. We study a composite of single-wall carbon nanotubes (SWCNT) with diamond nanoparticles and a SWCNT paper coated with nanocrystalline diamond films. The SWCNT paper serves here as a reference. We evaluate the surface free energy measured by contact angle technique, morphology imaged by scanning electron microscopy and the chemical composition determined by X-ray photoelectron spectroscopy, Raman spectroscopy at different excitation wavelengths and by attenuated total reflection (ATR) Fourier Transform Infrared spectroscopy (FTIR) using different ZnSe ATR prisms. We demonstrate that, because of the resonant nature of Raman process in SWCNTs, the particular conditions at Raman measurement (laser excitation wavelength, laser intensity) strongly influence the measured spectra of the sp 2 -sp 3 hybridized heterosystems. We also show how the dimensions of the ATR prism affect the results of the FTIR measurements of the SWCNT papers. Graphical abstract: